(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Over thelast 30 years, environmental education has been part of the curriculum in Southwest Florida public schools. Curriculum objectives,such as, environmental attitude,knowledge, and awareness (AKA), have been investigatedin the literature as ways to improvethe overall behavior of future citizenstoward the environment. The purpose ofthis study was to evaluate the aforementionedobjectives among the followinggroups: environmental specialists,high school instructors, high schoolstudents, and the parents of thecorresponding students in Bhopal during the 2009-20010 school year. An instrument was developed to measure the groups levels of awareness,knowledge, and attitude as well as theirlevels of self-efficacy. The returned surveysrepresented responses from: 27environmental specialists, 15 high school instructors, 224 high schoolstudents, and 222 parents. This studyfound statistically significant differences among the groups regarding the levels of awareness, knowledge, and attitude as related to environmental issues. The environmentalspecialists scored highest for all AKA componentsas compared to the lowest levelspresented by parent awareness, parent attitude, and high school student knowledge.In addition, factors such as socioeconomic status, ethnicity, and preference of leisure activities resultedin differences among the groupsregarding their levels of environmental AKA. This study supports theevaluation of AKA levels among participants as an appropriateapproach to the evaluation of environmentalcurriculum objectives. In addition,the study suggests a simplified measurement of AKA as an attempt to unify the parametersmeasured by numerous instrumentsfound throughout environmental education literature. The results of this study mayassist environmental specialists, instructors, and school districts in theevaluation of environmental education curricula.